Modelling internal management systems and supply chain effectiveness in state-owned enterprises in a developing economy - Nematatani, Pfanelo (Vaal University of Technology, 2022)
Although state-owned enterprises (SOEs) play an important role in the economies of many developed and developing countries, the majority fail to be sustainable. Most SOEs fail to contribute efficiently or effectively towards economic growth or the delivery of public services. Most South African SOEs are failing due to problems such as mismanagement, debt burden, underinvestment, depreciation of assets, poor corporate governance, and corruption. The failure of SOEs has led to a high increase in the cost of service they deliver, jobs losses, lowered investments and poor economic growth in South Africa. The aim of the study is to test a research model for internal management systems (IMS) and supply chain effectiveness in SOEs in a developing economy. A quantitative design was adopted in which a survey questionnaire was administered to 863 supply chain practitioners working in six South African SOEs. The collected data were analysed using descriptive statistics, exploratory factor analysis, Person Correlations and regression analysis. These tests are conducted using Statistical Package for Social Science (SPSS version 27.0). The study results showed significant positive relationships between organisation support development and total quality management, knowledge management and competitive advantage, behavioural integration and competitive advantage, safety management and competitive advantage, safety management and innovation, innovation and competitive advantage, total quality management and competitive advantage, total quality management and supply chain relationship commitment, competitive advantage and supply chain relationship commitment, innovation and supply chain relationship commitment, total quality management and supply chain effectiveness, competitive advantage and supply chain effectiveness and supply chain relationship commitment and supply chain effectiveness. The study concludes that the primary goal of SOEs in developing economies is to achieve a competitive advantage over their competitors. To achieve a position superior to that of their business competitors, they must first understand the strengths and weaknesses of their internal management, as well as the potential effects on supply chain effectiveness. Given the possibility that a study of this nature has not been performed before in South African SOEs, the results are an essential addition to the existing body of literature within the area of supply chain management (SCM) in SOEs in developing countries.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Internal management systems; Organisation support development; Knowledge management; Behavioural integration and safety management; Innovation; Total quality management; Competitive advantage; Supply chain relationship commitment; Supply chain effectiveness; Dissertations, Academic -- South Africa.; Business logistics.; Government business enterprises.; Developing countries.